Global incidence and prevalence of differentiated thyroid cancer in childhood: systematic review and meta-analysis - Moleti, Mariacarla; Aversa, Tommaso; Crisafulli, Salvatore; Trifirò, Gianluca; Corica, Domenico; Pepe, Giorgia; Cannavò, Laura; Di Mauro, Maria; Paola, Giuseppe; Fontana, Andrea; Calapai, Fabrizio; Cannavò, Salvatore; et al. (Frontiers in Endocrinology, 2023)
Objective: Differentiated thyroid cancer (DTC) is rare in childhood and adolescence, although representing the most frequent endocrine malignancy in this population. DTC includes both papillary thyroid carcinoma (PTC) and follicular thyroid carcinoma (FTC). Most pediatric DTC are PTCs, while FTCs are rare. To date, no systematic reviews on the global epidemiology of pediatric and adolescent DTC have been published. This systematic review and meta-analysis aims to estimate the overall incidence and prevalence of DTCs in patients aged 0-19 years. Methods: The systematic research was conducted from January 2000 to December 2021 through MEDLINE via PubMed, Cochrane Library and EMBASE databases. Two separate meta-analyses were performed for PTC and FTC. Results: After the selection phase, a total of 15 studies (3332 screened) met the inclusion criteria and are reported in the present systematic review. Five studies were conducted in Europe, five in North America, two in South America, one in Asia, one reported data for 49 countries and territories across the five continents and one from both USA and Africa. Most of the studies (n=14) reported data obtained from national registries and only one provided information collected from hospital medical records. Beyond the actual trend over time, our study reported a pooled global incidence rates (IRs) of PTC and FTC in the pediatric age of 0.46 (95% CI:0.33-0.59] and 0.07 (95% CI:0.02-0.12) per 100,000 person-years, respectively. The highest IRs were recorded among Caucasian girls, and the lowest in black or other races/ethnicities. Conclusions: Our data confirm that DTC in the pediatric population is a rare condition. The pooled IRs of the studies included in this meta-analysis are ~0.5 for PTC, which is the most common histological type when both genders and all age groups are considered. The implementation of a prospective international registry on pediatric DTC, as a part of the wider European Registries for Rare Endocrine Conditions, has been recently proposed. In addition to providing relevant information on the clinical behavior of this rare disease, standardization of data collection will be pivotal to fill current gaps and allow an accurate estimation of the real incidence and risk factors of DTC.